2012
DOI: 10.1039/c2cc31037f
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanines: a new class of G-quadruplex-ligands with many potential applications

Abstract: A G-quadruplex is a four-stranded DNA structure featuring stacked guanine tetrads, G-quartets. Formation of a G-quadruplex in telomere DNA can inhibit telomerase activity; therefore, development of G-quadruplex-ligands, which induce and/or stabilize G-quadruplexes, has become an area of great interest. Phthalocyanine derivatives have substantial potential as high-affinity G-quadruplex-ligands because these planar chromophores are similar in size and shape to the G-quartets. Here, we focus on the latest finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
95
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 149 publications
0
95
0
Order By: Relevance
“…It is striking to note that negatively charged compounds such as Nmethylmesoporphyrin IX (NMM) [44,45,132,133], protoporphyrin IX [134], hemin (Fe IIIprotoporphyrin IX) [135][136][137] with two carboxylic groups or tetraphtalocyanines with four sulfonate groups [138][139][140] are endowed with G-quadruplex binding capability. Since negatively charged molecules are devoid of any affinity for double-stranded DNA due to strong electrostatic repulsion, negatively charged aromatic molecules that are able to undergo external stacking with a G-quartet have a chance to be G-quadruplex selective [138,140].…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 98%
“…It is striking to note that negatively charged compounds such as Nmethylmesoporphyrin IX (NMM) [44,45,132,133], protoporphyrin IX [134], hemin (Fe IIIprotoporphyrin IX) [135][136][137] with two carboxylic groups or tetraphtalocyanines with four sulfonate groups [138][139][140] are endowed with G-quadruplex binding capability. Since negatively charged molecules are devoid of any affinity for double-stranded DNA due to strong electrostatic repulsion, negatively charged aromatic molecules that are able to undergo external stacking with a G-quartet have a chance to be G-quadruplex selective [138,140].…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 98%
“…The search for new molecules able to stabilize G4s has become an active field of research in anti‐cancer drug design . This includes notably planar π‐conjugated molecules, porphyrins and phthalocyanine derivatives, and coordination complexes . It has been demonstrated that coordination complexes (e.g., with Ru II , Ni II , Zn II , Mn III metal centers) can strongly and selectively interact with DNA G4 .…”
Section: Introductionmentioning
confidence: 99%
“…To understand how these ligands actually influence on dsDNA, RNA and other forms of DNA functions, in particular highly ordered structures that may be formed by the folded DNA chain has also essential application in chemical biology and medicinal chemistry [3,4]. The nonspecific binding makes difficult for drugs applications related to folded DNA because dsDNA coexist and could prevent the interaction between ligand and target structure [5,6]. The specificity of a ligand may be evaluated from the comparison of affinity to a site and cooperativity during binding of a ligand to the DNA oligomer vs. the DNA polymer [7].…”
Section: Introductionmentioning
confidence: 99%